Numerical simulations of cone penetration test in gassy sand deposits (2017)
ensification of loose granular deposits with blast densification technique isusually verified with measurements of ground surface settlement and by comparison of penetration resistance with field tests performed after and before treatment. Field test ssuch as the Standard Penetration Test (푆푃푇) and Cone Penetration Test (퐶푃푇)are ommonly employed. Recent field performance data has shown SPT and CPT measurements after blasting lower than the values before treatment. It indicates that the soil mass has not been improved, in terms of strength, despite the treated ayer significantly settled after blasting. This phenomenon is a ttributed to factors such as loss of aging, redistribution of stress, particle rearrangement and gas bubbles trapped in the soil mass released by detonations. This research focused on numerically studying the effect of gas bubbles trapped in the soil mass on the penetration resistance measured with the CPT. Boundary value problems simulating edometer, triaxial and CPT tests were performed with the finite element code PLAXIS 2D. The hypoplastic sand model with the intergranular strain extension was used to model the constitutive response of the sand more fluid compressibility is modified to account for the resence of free gas into the soil structure. Results from the field and numerical analyses were combined to draw conclusions and provide recommendations. It was found that the increases of the pore fluid compressibility reduce, especially for loose to medium sands, the cavity expansion pressure which is directly related to the CPT tip resistance